PLATELET INDICES IN PULMONARY TUBERCULOSIS. - POORANA PRIYA.P,; SUBHASHREE A.R, (International Journal of Pharma and Bio Sciences, 2014)
Studies have highlighted the occurrence of Reactive thrombocytosis during the active phase of pulmonary tuberculosis. Role of platelets in inflammatory response is attributed as the cause. But very few studies have demonstrated changes in Platelet related indices in such cases. Hence we aimed to study the relation between platelet indices and an acute phase reactant, Erythrocyte sedimentation rate in newly diagnosed cases of pulmonary tuberculosis. Our study included a total of 150 newly diagnosed cases of pulmonary tuberculosis showing sputum positivity for mycobacterium tuberculosis .In such cases, platelet parameters were correlated with erythrocyte sedimentation values. We found statistically significant positive correlation between Plateletcrit and erythrocyte sedimentation rate in active cases of pulmonary tuberculosis.